Medan City Development Planning and Challenges and Solutions in City Development Planning - Grace, Shania; Padang, Ratnauli; Saskia, Dwi Putri; Lapian, Inez Adelia; Simanjuntak, Syaloom Lestari; Panggabean, Fitri Yani (Formosa Journal of Sustainable Research, 2025)
The research method used in this study is the literature review method. Research articles collected in this study used manual searches via Google Scholar with the keyword "Development Planning". The results of the study indicate that the Medan City BAPPEDA has shown good performance in carrying out its duties and functions, but is still faced with problems such as minimal community participation and less than optimal performance effectiveness. Age, education, employment, the COVID-19 pandemic, crime, and natural disasters are obstacles. To increase the economic capacity of Medan City, an effective development planning strategy is needed with a focus on infrastructure, adaptive economic policies, human resource development, effective governance, and development of the local economic sector. Therefore, improvements need to be made through education, public awareness, optimization of Bappeda performance, and coordination between stakeholders to achieve inclusive and sustainable development The research method used in this study is the literature review method. Research articles collected in this study used manual searches via Google Scholar with the keyword "Development Planning". The results of the study indicate that the Medan City BAPPEDA has shown good performance in carrying out its duties and functions, but is still faced with problems such as minimal community participation and less than optimal performance effectiveness. Age, education, employment, the COVID-19 pandemic, crime, and natural disasters are obstacles. To increase the economic capacity of Medan City, an effective development planning strategy is needed with a focus on infrastructure, adaptive economic policies, human resource development, effective governance, and development of the local economic sector. Therefore, improvements need to be made through education, public awareness, optimization of Bappeda performance, and coordination between stakeholders to achieve inclusive and sustainable development